(untitled) (One Health & Risk Management, 2024)
Introduction. The population of all countries of the world was affected by the COVID-19 pandemic, but the most severe consequences were for low- and middle-income countries (LMICs). Following Russia’s invasion of Ukraine, there have changes in people’s attitudes to the challenges posed by the COVID-19 pandemic. The aim is to study the attitude of young people to the problem of COVID-19, influenza, and other upper respiratory infections (URI) during the war in Ukraine. Material and methods. The materials consist of the results of an online survey of young people in Chernivtsi and neighboring regions of the western part of Ukraine in 2023/2024 (N=269). The methods of sociological analysis, descriptive statistics, pair correlation, and logistic regression using PIVOT and SPSS were applied. Results. According to the results, 65.1% of respondents suffered from COVID-19, with 70.3% of them being vaccinated. During the pandemic, only 4.2% of respondents admitted that they did nothing to prevent infection. Since the beginning of the war, this percentage increased to 43.2%, with an additional 8.2% citing a lack of opportunity for prevention. At the end of the second year of the war, only 25.7% of respondents expressed concern about COVID-19, influenza, and other URIs. A direct correlation was found between this concern and the problem of restricting men’s travel abroad during the pandemic (r=0.239), psychological issues (r=0.198), and financial problems (r=0.224) among females. Female anxiety was also influenced by job loss (r=0.152) and engagement in activities such as volunteering in aid delivery to the front (r=0.288) and cooking food for soldiers (r=0.152). Significance was established at the 95% CI, p<0.05. Conclusions. At the end of the second year of the war, the situation with COVID-19, influenza and other URIs was a concern of only one in four respondents (25.7%), which was also associated with vaccination (70%) and a transmitted disease (65%).